DYNAMICS OF QUANTITY AND STRUCTURE OF ORTHOPTERA OF KARACHEVO-CERKESS REPUBLIC - G. M. ABDURAKHMANOV; O. A. KALACHYOVA; Z. S. TEMIRLIEVA (Юг России: экология, развитие, 2015)
The work is detailed description of different biotopes, dynamics of quantity and structure of grasshoppers